Adverse childhood experiences and trajectories of internalizing, externalizing, and prosocial behaviors from childhood to adolescence. (February 2021) - Bevilacqua, Leonardo; Kelly, Yvonne; Heilmann, Anja; Priest, Naomi; Lacey, Rebecca E.
Highlights: Adverse childhood experiences (ACEs) predict poorer mental health. Multiple ACEs predict much poorer mental health than a single ACE. Parental discord & parental depression predict internalizing problems in particular. Harsh parenting & physical punishment predict externalizing problems in particular. Harsh parenting & physical punishment predict lower prosocial behavior in particular. Abstract: Background: Adverse childhood experiences (ACEs) predict poorer mental health across the life course but most of the extant research has employed ACE scores or individual adversities using retrospective data. Objectives: To study the impact of ACEs on later mental health using not only ACEs scores and individual ACEs, but also latent class analysis (LCA), which respects the clustering of adversities. Participants and setting: 8823 members from the UK Millennium Cohort Study. Methods: We investigated the impact of prospectively reported ACEs on mental health trajectories derived using the Strengths and Difficulties Questionnaire at age 3, 5, 7, 11 and 14. Associations between LCA-derived ACE clusters, ACE scores, individual ACEs and mental health trajectories were tested using linear mixed effects models. Results: With statistical significance set at 5% level, ACE scores showed a graded association with internalizing (ACE score of 1: β = 0.057; ACE score of 2: β = 0.108; ACE score of 3: β = 0.202), externalizing (ACE score of 1: β = 0.142; ACE score of 2: β = 0.299; ACE score of 3: β = 0.415) and prosocial behaviors (ACE score of 1: β=-0.019; ACE score of 2: β=-0.042; ACE score of 3: β=-0.059). Harsh parenting and physical punishment were particularly strongly associated with externalizing (β = 0.270 and β = 0.256) and negatively associated with prosocial behaviors (β=-0.046 and β=-0.058). Parental discord and parental depression showed the strongest associations with internalizing problems (β = 0.125 and β = 0.113). LCA did not discriminate ACE clusters in this dataset. Conclusions: ACEs have an important impact on mental health from childhood to adolescence. ACEs score approach yielded useful results, which were further enhanced by exploring individual ACEs.